Netherland - O'Neill, Joseph (Harper Perennial, 2009)
Alone in New York, Dutchman Hans van den Broek seeks refuge in the game of his childhood - cricket. Years later a friend is found murdered and Hans is forced to remember his unlikely friendship with Chuck - a dreamer, visionary, and perhaps something darker 2009.